Current Problems of Modern Cardiology: Why Is Hypertension Getting Younger? - Oybekova G.S; Khuzhamberdiev M.A; Vakhabov B.M. (Genius Journals, 2023)
The review article presents data on the prevalence of arterial hypertension in young people, pathogenetic mechanisms and peculiarities of diagnosis.
Keywords: Arterial hypertension; risk factors; young age